Testing the limits: Investigating the effect of tDCS dose on working memory enhancement in healthy controls - Hoy, Kate E.; Emonson, Melanie R.L.; Arnold, Sara L.; Thomson, Richard H.; Daskalakis, Zafiris J.; Fitzgerald, Paul B. (Neuropsychologia, 2013)
Transcranial Direct Current Stimulation (tDCS) is a non-invasive form of brain stimulation which has been shown to induce changes in brain activity and subsequent functioning. In particular, there is a rapidly growing evidence base showing that anodal tDCS applied to the left prefrontal cortex (PFC) is able to enhance aspects of cognitive functioning, in particular working memory (WM). This has led to both excitement and concerns regarding the possibility of ‘electrodoping’ in order to greatly improve one's cognitive performance. We investigated the behavioural and neurophysiological effects of increasing the current (or ‘dose’) of tDCS on the degree of WM improvement in healthy controls. Single sessions of 1mA, 2mA and sham anodal tDCS to the left PFC were undertaken over a period of three weeks. Participants underwent a WM task at three time points post-stimulation (0, 20 and 40min) with concurrent electrophysiological (EEG) recordings. Our results showed that while active tDCS can enhance behavioural performance, with neurophysiological findings indicating improve efficiency of cognitive processing; we showed that 1mA produced the most significant effects. These findings are somewhat unexpected as tDCS dose effects in cognitive enhancement have been shown previously in patient populations. Our results provide valuable information regarding the potential limits of tDCS induced cognitive enhancement in healthy controls, as well as providing additional insights into the possible mechanisms of action of tDCS. •We examined the effect of tDCS dose on the degree and duration of enhancement.•Active left PFC anodal tDCS enhances accurate reaction time on the 2back.•Effects were most significant, and occurred most rapidly, following 1mA.•tDCS produced neurophysiological changes consistent with more efficient processing.•Increasing tDCS dose does not lead to greater or longer lasting effects in controls.